2018
DOI: 10.1016/j.jaerosci.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Particle precipitation by bipolar corona discharge ion winds

Abstract: The paper reports the development of a particle precipitation based aerosol sampler using bipolar corona discharge ion winds with collected particles of minimized net charge. For the new approach, neutralized particles move towards a sampler under the effect of electric field and dual ion winds. Since there is no electrode or sampling chip installed inside the air-flow channel, impediments to airborne particle flow or ion winds are removed along the flow direction. In addition, the isolation of ion winds, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Experimental and numerical studies have demonstrated a good agreement in the size range of 0.3 μm -10 μm (Goo and Lee 1997, Park and Kim 2000, Dau, Dinh et al 2018. Multiple experimental studies for the PM in size range of 30 nm -400 nm (Yoo, Lee et al 1997, Miller, Frey et al 2010, Dey and Venkataraman 2012, Roux, Sarda-Estève et al 2016) agree with the theoretical models.…”
Section: Introductionsupporting
confidence: 56%
“…Experimental and numerical studies have demonstrated a good agreement in the size range of 0.3 μm -10 μm (Goo and Lee 1997, Park and Kim 2000, Dau, Dinh et al 2018. Multiple experimental studies for the PM in size range of 30 nm -400 nm (Yoo, Lee et al 1997, Miller, Frey et al 2010, Dey and Venkataraman 2012, Roux, Sarda-Estève et al 2016) agree with the theoretical models.…”
Section: Introductionsupporting
confidence: 56%
“…a two orders of magnitude smaller than a typical corona discharge, to minimize the unexpected effect such as streamer discharge. In our previous work, we proved that a current of ~2 µA is sufficient to generate strong ionic wind that can manipulate the movement of micro-/nano-particles [53,54].…”
Section: Electrohydrodynamic Simulationmentioning
confidence: 95%
“…Thus, different approach to fabricate micro/nano particles has been studied intensively to suit biomedical applications. Electrohydrodynamic techniques such as electrospraying, and electrospinning are a potential scheme in generating or collecting nanostructured materials [4] [5]. However, due to being highly charged, particles fabricated by those techniques require a grounded electrodes as collector (Fig.…”
Section: Introductionmentioning
confidence: 99%